Fungal sensitization and positive fungal culture from sputum in children with asthma are associated with reduced lung function and acute asthma attacks respectively. Issue 6 (13th December 2020) - Welsh, Kathryn G.; Holden, Karl A.; Wardlaw, Andrew J.; Satchwell, Jack; Monteiro, William; Pashley, Catherine H.; Gaillard, Erol A.
Abstract: Background: Sensitization to thermotolerant fungi, including filamentous fungi and Candida albicans, is associated with poor lung function in adults with severe asthma. Data in children are lacking. Environmental exposure to fungi is linked with acute severe asthma attacks, but there are few studies reporting the presence of fungi in the airways during asthma attacks. Methods: We investigated the association between fungal sensitization and/or positive fungal sputum culture and markers of asthma severity in children with chronic and acute asthma. Sensitization was determined using serum‐specific IgE and skin prick testing against a panel of five fungi. Fungal culture was focused towards detection of filamentous fungi from sputum samples. Results: We obtained sensitization data and/or sputum from 175 children: 99 with chronic asthma, 39 with acute asthma and 37 controls. 34.1% of children with chronic asthma were sensitized to thermotolerant fungi compared with no children without asthma ( p =< 0.001). These children had worse pre‐bronchodilator lung function compared with asthmatics without sensitization including a lower FEV1 /FVC ratio ( p < .05). The isolation rate of filamentous fungi from sputum was higher in children with acute compared with chronic asthma. Conclusions: Fungal sensitization is a feature of children with chronic asthma. Children sensitized to thermotolerant fungi have worse lung function, require more courses of systemic corticosteroids and have greater limitation of activities due to asthma. Asthma attacks in children were associated with the presence of filamentous fungi positive sputum culture. Mechanistic studies are required to establish whether fungi contribute directly to the development of acute asthma.